Deflation Risk - Fleckenstein, Matthias; Longstaff, Francis A.; Lustig, Hanno (Review of Financial Studies, 2017)
We study the nature of deflation risk by extracting the objective distribution of inflation from the market prices of inflation swaps and options. We find that the market expects inflation to average about 2.5% over the next 30 years. Despite this, the market places substantial weight on deflation scenarios in which prices significantly decline over extended horizons. The market prices the economic tail risk of deflation similarly to other types of tail risks, such as corporate default or catastrophic insurance losses. We find that deflation risk is strongly negatively correlated with outcomes in the financial markets and with consumer confidence.